Structural Analysis Of The Short Story “Roqisoh Al-Ma’bad” By Taufiq Al-Hakim In The Aspect Of Literary Means - Kusumawardani, Indah Dian (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article aims to analyze the intrinsic elements in the short story titled "The Temple Dancer" (raqisat al-ma'bad) by Tawfiq al-Hakim. This research employs a descriptive qualitative method using Robert Stanton’s structural approach, which emphasizes the intrinsic elements of a literary work—specifically characterization, plot, and theme as a unified whole. The primary source of this research is the short story itself. Data collection techniques include close reading and note-taking. The results indicate that the story utilizes a progressive plot interspersed with the protagonist's internal reflections, while secondary characters serve as catalysts for conflict and character development. The setting shifts from a train journey across Europe to the atmosphere of Paris. Furthermore, the story employs a first-person point of view, providing psychological depth to the narrative. In conclusion, the strength of this short story lies in its dynamic characterization. Moreover, the integration of plot and theme conveys a profound philosophical meaning regarding the relationship between humanity, art, and love.